2017
DOI: 10.5155/eurjchem.8.4.410-416.1650
|View full text |Cite
|
Sign up to set email alerts
|

N-(Dibenzylcarbamothioyl)-3-methylbutanamide: Crystal structure, Hirshfeld surfaces and antimicrobial activity

Abstract: The compound N-(dibenzylcarbamothioyl)-3-methylbutanamide as a thiourea derivative was synthesized and structurally characterized by NMR and FT-IR spectroscopic techniques. The molecular structure of compound was also characterized by single crystal X-ray diffraction method. Crystal data for title compound C20H24N2OS: monoclinic, space group C2/c (no. 15), a = 19.6882(9) Å, b = 9.4045(4) Å, c = 19.5012(8) Å, β = 98.433(2)°, V = 3571.8(3) Å3, Z = 8, μ(CuKα) = 1.665 mm-1, 25057 reflections measured (9.168° ≤ 2Θ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
(53 reference statements)
2
2
0
Order By: Relevance
“…When the frequencies of the functional groups in the structure of the ligands were examined, the stretching frequencies of the NH groups were recorded in the range of 3263–3372 cm −1 for the H 2 L 1-5 compounds [ 30 , 31 ]. The stretching vibrations detected at 1672, 1673, 1673, 1671, and 1666 cm −1 for the H 2 L 1-5 ligands, respectively, are assigned to the carbonyl ν (C O) stretching vibration mode and these results are in agreement with previous studies [ [32] , [33] , [34] ]. In agreement with previous work [ 34 ], the IR frequencies of the ν (C Ar -H) group in the structure of the compounds were monitored in the range of 3078–3113 cm −1 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…When the frequencies of the functional groups in the structure of the ligands were examined, the stretching frequencies of the NH groups were recorded in the range of 3263–3372 cm −1 for the H 2 L 1-5 compounds [ 30 , 31 ]. The stretching vibrations detected at 1672, 1673, 1673, 1671, and 1666 cm −1 for the H 2 L 1-5 ligands, respectively, are assigned to the carbonyl ν (C O) stretching vibration mode and these results are in agreement with previous studies [ [32] , [33] , [34] ]. In agreement with previous work [ 34 ], the IR frequencies of the ν (C Ar -H) group in the structure of the compounds were monitored in the range of 3078–3113 cm −1 .…”
Section: Resultssupporting
confidence: 92%
“…The stretching vibrations detected at 1672, 1673, 1673, 1671, and 1666 cm −1 for the H 2 L 1-5 ligands, respectively, are assigned to the carbonyl ν (C O) stretching vibration mode and these results are in agreement with previous studies [ [32] , [33] , [34] ]. In agreement with previous work [ 34 ], the IR frequencies of the ν (C Ar -H) group in the structure of the compounds were monitored in the range of 3078–3113 cm −1 . The data obtained from the FTIR study are compatible with the literature [ [35] , [36] , [37] ] and these data confirmed the structure of the prepared NNN pincer type compounds.…”
Section: Resultssupporting
confidence: 92%
“…For example N-(alkyl/aryl)-N'-acylthiourea and N-di(alkyl/aryl)-N'-acylthiourea derivatives which have oxygen, nitrogen and sulphur donor atoms, exhibit prevalent coordination modes. Organic ligands that have thiourea moiety are able to bind metal ions in several ways, like: (i) acting as monodentate ligands through sulphur atom in mononuclear complexes [1-4] (ii) binding to metal ions forming S-bridges in dinuclear complexes [4][5][6][7][8] or (iii) chelating sulphur and nitrogen atoms [4][5][6][8][9][10][11][12][13][14][15][16] Thiourea derivatives as a ligand have a large dipole moment and these ligands can also form extensive network of hydrogen bonds due to their unique structures. For example in 3-monosubstituted arylthioureas [17][18][19], the carbonyl group and the proton on the nitrogen attach in a strong hydrogen bond interaction which unite into a planar six-membered ring structure forming an "S" shaped conformation of the C=O and C=S groups [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The bond distances of C1-N1 = 1.325(5), C8-N1 = 1.352(5) Å in the coordinated benzoylthiourea ligand are significantly shorter than the average length of a single C-N bond (1.48 Å). [55][56][57][58] Furthermore, the carbonyl and thiocarbonyl bond distances (O1-C1 = 1.267(5) and S1-C8 = 1.740 (4) Å) of the coordinated ligand are longer than the bond lengths of the corresponding double bond distances of the benzoylthioureas, [58][59][60][61][62][63] and these data show electron delocalization within the chelate ring.…”
Section: Crystallographic Studiesmentioning
confidence: 99%